Determinan Partisipasi Keluarga Berencana Pada Keluarga Pra Sejahtera di Provinsi Sumatera Selatan: Survei Demografi dan Kesehatan Indonesia - Dio Febria (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
The great number of the population in Indonesia could create several negative impacts such as: health, poverty, unemployment, and crime problems. Family Planning program (FP) has implication in decreasing natality rate in order to enhance social wealth. In 2012, FP participation rate of pre-prosperous family in South Sumatera Province (24%) is greater than that of the prosperous I, II, III, and III+ family. Thus, the purpose of this research is analyzing which factors determining FP participation rate of pre-prosperous family in South Sumatera Province. The research is a quantitative analysis using secondary data from Demographic and Health Survey (DHS) of Indonesia 2012, analysed by logistic regression. The result shows that two variables significantly affecting FP participation rate are the number of children and age of the husband. The number of children is a positive coefficient meaning that number of children (> 2 children), the higher probability of a wife to participate in family planning. Age of husband is a negative coefficient meaning that the younger the husband’s age, the higher probability of a wife to participate in family planning. In contrast, other variables, namely: age of wife, education of wife, wife’s participation in work, residence, size of the ideal family, communication between wife and husband, and number of visits of FP officer do not significantly affect the FP participation rate of wife. Government should socialize FP program for early stage of marriage, so that the pre-prosperous family would participate in the FP program before they have many children. In addition, further research is needed on the effectiveness of the most used contraception (pill and contraceptive injection) on the pre-prosperous family. Keywords: family planning, pre-prosperous family, number of children, age of husband